Living Paradox in Riverine Bangladesh: Whiteheadian Perspectives on Ganga Devi and Khwaja Khijir - Khan, Naveeda (Anthropologica, 2017)
We begin with the words of rural and riverine women from Bangladesh recalling the events of their children’s deaths by drowning. These events are cast as the work of supernatural beings, specifically Ganga Devi and Khwaja Khijir, who compel the mothers into forgetfulness and entice the children to the water. Is this a disavowal of loss and responsibility? This article considers that the women, specifically those from northern Bangladesh, assert not only their understanding of the losses that they have suffered but also their changing relationship to the river and its changing nature through their evocations of mythological figures. Alongside the many experiences of the river, the article takes note of its experience as paradoxical, with paradoxicality serving as the occasion for the coming together of the mythological, the material, and the social. The article draws upon Alfred North Whitehead to interrelate the strata of myths and their permutations, with the women’s experiences of the river, and the river as a physical entity, allowing us to explore how the women’s expressions portend the changing climate.